Assessing the relative informativeness and permanence of pro forma earnings and GAAP operating earnings - BHATTACHARYA, Nilabhra (Institutional Knowledge at Singapore Management University, 2003)
This study investigates whether market participants perceive pro forma earnings to be more informative and more persistent than GAAP operating income by analyzing a sample of 1,149 actual pro forma press releases. We find that pro forma announcers report frequent GAAP losses and are mostly concentrated in the service and high-tech industries. Our analyses of short-window abnormal returns and revisions in analysts’ one-quarter-ahead earnings forecasts indicate that pro forma earnings are more informative and more permanent than GAAP operating earnings. Our evidence suggests that market participants believe pro forma earnings are more representative of “core earnings” than GAAP operating income.